Effects of energy-based ablation on thyroid function in treating benign thyroid nodules: a systematic review and meta-analysis. (1st January 2020) - Fei, Yuan; Qiu, Yuxuan; Huang, Dong; Xing, Zhichao; Li, Zhe; Su, Anping; Zhu, Jingqiang
Abstract: Background: Whether thyroid function would be affected by ablation remains controversial. This systematic review and meta-analysis aimed to investigate the effects of energy-based ablation on thyroid function in treating benign thyroid nodules. Methods: EMBASE, PubMed, Cochrane Library, and Web of Science databases were searched. The mean difference (MD) or standard MD (SMD) was applied to assess changes in thyroid function, thyroglobulin (Tg), and antibodies after ablation. RevMan version 5.3 was used for data synthesis. Results: Forty-two studies involving 6380 patients were eligible. The pooled results revealed significant decrease of 1-day thyroid-stimulating hormone (95% CI, −0.67 to −0.14), significant increase of 1-day, 1-week, and 1-month free thyroxine (95% CI, 1.57 to 5.28; 95% CI, 0.61 to 2.42; 95% CI, −0.76 to −0.15), 1-day and 1-week Tg level (95% CI, 0.40 to 0.81; 95% CI, 0.21 to 1.29), 6-month anti-thyroglobulin antibodies (95% CI, 0.02 to 0.26), 1- and 3-month thyroperoxidase antibody (95% CI, 0.02 to 0.22; 95% CI, 0.17 to 0.43), and 1-day, 1-, and 3-month thyrotrophin receptor antibody (95% CI, 0.10 to 0.43; 95% CI, 0.00 to 0.30; 95% CI, 0.13 to 0.36) after ablation. No statistically significant differences were found in these six indicators in the longer term. The results of subgroup analysis were similar to the pooled results. No significant publication bias was found. Conclusions: Energy-based ablation was more likely to have negative effects on thyroid function and antibodies and led to transient increase in Tg level in the short term. However, most of the patients would not develop any thyroid dysfunction in the long-term follow-up.